Nursing Student's Attitudes toward Their Future Career in nursing faculty Kabul University of Medical Sciences - Ahmadi, Abdul Qudoos; Haidari, Noorulhaq; Nazari, Rajab; Hosianpoor, Zakir Hosain (Technium Social Sciences Journal, 2022)
Abstract. Background: a positive attitude toward a future career not only leads to job satisfaction and success but can also lead to the development of the community in which one serves. Due to the importance of medical fields, the appropriate attitude of students towards their future careers can be the basis of the physical, mental, and psychological health of human beings with the emergence of traits such as compassion and interest. Objective: The goal of this study is to assess the Nursing Students` attitude level toward their future careers at Kabul University of Medical Sciences “Abo Ali ibn Sina” in 2021. Methodology: A cross-sectional descriptive study was conducted among 249 nursing students at Kabul University of Medical Sciences “Abo Ali ibn Sina” by census sampling method. The data collection tool was the University of Minnesota Questionnaire based on the Likert scale. Data were coded and analyzed using Statistical Package for Social Science (SPSS25) software. Results: The Mean and standard deviation of students' attitudes towards their future careers were 17.78±5.351 respectively. Which was lower than the mean exam score (18). In total, 122 (49.0%) participants had a negative attitude, 107 (43.0%) had a positive attitude, and 20 (8.0%) students were neutral towards their future careers. Conclusion: The mean score for the attitude of the population under investigation toward their future career was lower than the acceptable level which demonstrates they do have not an acceptable attitude toward their future career.